Kinematical and physiological responses of overground running gait pattern at different intensities - Monteiro, A. S.; Galano, J. P.; Cardoso, F.; Buzzachera, C. F.; Vilas-Boas, J. P.; Fernandes, R. J. (Sensors, 2024)
Runners achieve forward locomotion through diverse techniques. However, understanding the behavior of the involved kinematical variables remains incomplete, particularly when running overground and along an intensity spectrum. We aimed to characterize the biomechanical and physiological adaptations while running at low, moderate, heavy and severe intensities. Ten middle- and long-distance runners completed an incremental intermittent protocol of 800 m steps until exhaustion (1 km·h-1 velocity increments and 30 s intervals) on an outdoor track field. Biomechanical data were captured using two high-resolution video cameras, and linear and angular kinematic variables were analyzed. With the intensity rise, a decrease in stride, step and contact times ([0.70-0.65], [0.35-0.33] and [0.42-0.37] s) and an increase in stride length and frequency and flight time ([3.13-3.52] m, [1.43-1.52] Hz and [0.28-0.29] s; p < 0.05) were observed, together with an increase in oxygen uptake and blood lactate concentrations ([54.7-67.6] mL·kg-1·min-1 and [3.1-10.2] mmol·L-1). A more flexed hip at initial contact and toe-off (152.02-149.36] and [165.70-163.64]) and knee at initial contact ([162.64-159.57]; p < 0.05) were also observed. A consistent gait pattern along each protocol step was exhibited, with minor changes without practical significance. Runners are constantly adapting their gait pattern, reflected in both biomechanical and physiological responses, both of which should be considered for better characterization.